NUTRACEUTICAL, PROXIMATE, AND SENSORY QUALITIES OF READY-TO-CONSUME BAMBARA GROUNDNUT DAIRY SUBSTITUTE SUPPLEMENTED WITH BULLOCK AND GINGER POWDER - Irondi, Emmanuel Anyachukwu; Aina, Hope; Sulyman, Abdulhakeem; Imam, Yunus; Awoyale, Wasiu; Ajani, Emmanuel (Food and Feed Research, 2026)
Plant-based dairy substitutes have gained significant attention recently due to consumers’ growing demand for healthier food options. This study evaluated the nutraceutical, proximate and sensory qualities of ready-to-consume Bambara groundnut milk substitute (BGMS) supplemented with bullock and ginger, as natural supplements. BGMS was formulated from Bambara groundnut flour and supplemented with an optimised proportion of one of the bullock, ginger, and bullock-ginger blends to obtain milk substitutes, coded BGMS-B, BGMS-G, and BGMS-BG, respectively, with BGMS (without any natural additive) as the control. Each sample was freeze-dried to obtain a ready-to-consume BGMS. Bioactive constituents (total flavonoids, tannins, total phenolics and total saponins), enzyme (pancreatic lipase, alpha-amylase, alpha-glucosidase and angiotensin I-converting enzyme (ACE)) inhibitory and antioxidant (ferric reducing power, ABTS•+ and DPPH•-scavenging) activities of the ready-to-consume BGMS samples were analysed. BGMS-B had the highest total flavonoids (0.98±0.01 mg/g), tannins (12.57±0.02 mg/g), total phenolics (23.49±0.52 mg/g) and saponins (25.82±1.71 mg/g) levels. It also exhibited the most potent inhibitory effects against pancreatic lipase (IC50: 329.53±0.03 µg/mL), alpha-glucosidase (IC50: 116.03±0.03 µg/mL), and ACE (IC50: 370.90±0.01 µg/mL), displaying the strongest antioxidant capacity. BGMS-G had the highest protein content (24.50±0.85%), while BGMS-B had the lowest fat (4.47±0.35%), ash (3.49±0.00%), and moisture content (5.99±0.78%). All the samples had overall sensory attributes acceptability above 5 points. Hence, supplementing the ready-to-consume BGMS with bullock and ginger enhanced its bioactive constituents, enzyme inhibitory and antioxidant capacities, making it a potential functional food.